Technical considerations for sampling ballast water to determine compliance with discharge performance standards - Loiacono, Stephen; Ceballos-Osuna, Lina; Scianni, Chris; Brown, Christopher W. (Frontiers in Marine Science, 2024)
In order to discharge ballast in waters of the USA and Member States of the IMO, a vessel must use a Type-Approved BWMS. Although rigorous efficacy testing is required to gain Type-Approval status, there are currently no requirements for regular compliance checks after a BWMS has been commissioned. Routine compliance checks, to enumerate organisms in treated discharges, are currently the only way to know if a system is meeting a BWDS. This policy brief has two objectives: 1) Highlight the importance of routine collection and analysis of treated ballast water discharges, and 2) Present technical considerations to perform compliance assessments, highlighting good practices for sample collection and analysis and advising of potential obstacles. These assessments are necessary to inhibit the spread of non-indigenous species.